Analysis of the Effectiveness of Using Active Filters and Passive Filters in Reducing Harmonics Using a Power Simulator (PSIM) at PT. Delta Jaya Mas - Reza Sarwo Widagdo; Puji Slamet Slamet; Cahyo Pangestu (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
The Extruder Machine at PT. Delta Jaya Mas plays a critical role in the production of rubber and PVC hoses, as well as molded rubber products. This process involves the use of a 3-phase synchronous motor and Variable Frequency Drive (VFD), which can introduce harmonics into the electrical system due to their non-linear load. These harmonics can cause waveform distortion, leading to decreased efficiency and potential equipment damage. To overcome this issue, a comprehensive research is being conducted utilizing the Power Simulator (PSIM) program to analyze the impact of harmonics and evaluate the effectiveness of both active and passive filters in reducing these unwanted distortions. Initial assessments of the Extruder SDP panel revealed elevated levels of Total Harmonic Distortion (THD) in the current phases, while the voltage phases remained within acceptable thresholds. Simulation results demonstrated that the active filter was able to significantly reduce THD to an impressive 1.57%, showcasing its effectiveness in harmonic mitigation. On the other hand, the passive filter also proved beneficial, albeit to a slightly lesser extent, achieving a reduction in THD to 34.07%. This ongoing research not only aims to assist PT. Delta Jaya Mas in implementing appropriate harmonic reduction measures for their Extruder Machine but also seeks to advance the understanding of harmonic analysis and filter applications.